Sintering of hydroxyapatite-bioglass ceramics composite from submicrometer powder - Phanlob Chankachang (2018)
The mechanical properties of hydroxyapatite ceramics was improved by adding 5 wt% of Ca-P-Na-based-glass to be as sintering aid and were made their powder to submicron sized. The powders are uniaxially compact and then sintering at 1300°C in air.Microstructure and mechanical properties of the ceramic composite products were investigated. It was found that the strength of hydroxyapatite composite was increased about 42% that of the sample which fabricated by micron sized HA composite powder having the same porosity and this values are in rang of values of the strength of the cortical human bone. Moreover, Young modulus values of 16.4± 1.8 GPa matched well with the Young modulus values of human bone, so it will not cause interfacial stress between implant and bone leading to good fixation of the materials. © (2013) Trans Tech Publications, Switzerland.